A process framework of shared leadership emergence in product development project teams - Maximilian Müller; Constanta-Nicoleta Bodea; Mladen Radujković (Project Leadership and Society (PLAS), 2023)
Shared leadership is a complex phenomenon as it is a dynamic, interactive, and cyclic process that is shared among several team members at different times. The focus of research on shared leadership is on the preconditions and consequences of shared leadership, but little is known about the process of its emergence. In our study, we take a process perspective to gain deep insights into the emergence of shared leadership. In an exploratory case study, data were collected through observation of team meetings, semi-structured interviews and internal project documents and analysed via a coding process and content analysis. Based on our findings, we develop a process framework for the emergence of shared leadership in a product development project team. We make several contributions. First, we extend the theory of shared leadership by adding a process framework for the emergence of shared leadership in product development project teams. Second, we enhance the leadership emergence theory to include additional antecedents and process mechanisms. Third, we extend the functional leadership theory by identifying the occurrence of leadership functions. The practical contributions we make are relevant for project managers/sub-project leaders and team members to promote and develop shared leadership in product development project teams.
Keywords: 650; Case study; Leadership emergence; Leadership function; Process framework; Product development project team; Shared leadership